The optimisation of bondcoat oxides for improved thermal barrier coating adhesion - Fisher, Gary Anthony (Cranfield University, 1998)
Superalloys used for the critical hot sections of modem aero-gas turbines . are designed primarily to exhibit good creep and fatigue resistance, coupled with toughness and microstructural stability. However, an optimum level of these properties can only be attained with a decrease in the oxidation and corrosion resistance of the alloy. This had led to the adoption of surface coatings to protect turbine blades against the corrosive environments in which they operate. The use of Thermal Barrier Coatings (TBCs) enables the design of more efficient and powerful gas turbines whilst still providing environmental protection for the blade. A TBC is a duplex coating system, combining a ceramic topcoat with a metallic bondcoat. The ceramic layer thermally insulates the turbine blade whilst the bondcoat protects the substrate from oxidation and corrosive attack. Central to the performance of a TBC is the integrity and adherence of the alumina scale promoted by the bondcoat. The scale acts to both bond the ceramic topcoat and to act as a barrier against environmental attack. This study aimed to optimise the oxide formed by the bondcoat and so increase the life of the TBC. This was achieved by investigating the effects of bondcoat pre-treatments and by the design and development of coatings to be used specifically as bondcoats. The performance of the systems was assessed using hot oxidation isothermal and cyclic tests and the coatings were analysed using a variety of techniques, including optical microscopy, SEM, XRD and the modified scratch test. The investigation of the effects of pre-treatments revealed that the pre-oxidation of bondcoats could help promote an initial alumina scale. However, any potential benefits were overshadowed by the degradation mechanisms inherent within the coating systems. This highlighted the importance of the composition and chemistry of the bondcoat in determining the properties of the alumina scale, the relevance of which was demonstrated in the bondcoat design element of the study. Both a platinum aluminide bondcoat and a novel diffusion-type bondcoat were developed and optimised. The performances of the systems were assessed and their degradation modes analysed, resulting in a range of bondcoats which outperform those currently available, making them ideal for the design of modem Thermal Barrier Coating systems.